Essays on business cycles, open economies and asset prices volatility - Pacharoni, Victor Alberto (ProQuest Dissertations & Theses, 2003)
This thesis is a collection of essays on open economy macrodynamics and asset price volatility as well as a methodology note on the genetic algorithm for solving computational models. The first essay is an analysis of a dynamic open economy. The paper examines the relationship of business cycles, the terms of trade and Tobin's q using a three-sector dynamic stochastic general equilibrium model for a small open economy. Results show the importance of terms of trade shocks for developing economies. The model is able to replicate 50 percent of the actual volatility of GDP and stock market indices. The parameterized expectation solution algorithm produces more accurate simulations, according to the Den Haan - Marcet statistic, than linear quadratic approximation. The second essay is about monetary policy in a similar type of open economy. The paper examines the outcomes of alternative targets of the Central Bank in different scenarios for a small open economy subject to terms of trade shocks. Two forms of stickiness of information are analyzed: when the central bank has to learn the evolution of the key variables to update its policy rules, and when there are different degrees of exchange rate pass-through. Results show that when there are feedback rules for the interest rate under low exchange rate pass-through and under “learning”, a combined inflation and output growth target yields higher welfare than a pure inflation target. A policy rule that focuses on Tobin's q, as well as inflation, is dominated by rules based on pure inflation or inflation and growth targets. The methodology note explain the use of the genetic algorithm. They represent a class of global search. Theses notes explain the steps for finding global optima in both static and dynamic environments.